Mediating Role of Infidelity-related Posttraumatic Symptoms in the Relationship Between Forgiveness and Psychological Health Concerns - Tauy, Jhunar John Magararo; Perez, Jeannie Agustin (Psikoislamika: Jurnal Psikologi Islam, 2023)
Infidelity is one of the most common concerns in romantic relationships and is deemed morally unacceptable. Such events can be disruptive and may lead to negative consequences on well-being of betrayed individuals. This study examined the prevalence of infidelity-related posttraumatic symptoms and psychological health concerns (i.e., depression, anxiety, stress) among young adults who experienced infidelity by their partners.  It also investigated whether forgiveness reduces the likelihood of psychological health concerns through lower levels of infidelity-related posttraumatic symptoms. It utilized a cross-sectional, predictive nonexperimental quantitative research design with n = 162 young adults, ages 19 – 40, who experienced being betrayed in a romantic relationship. The results showed that most of the respondents (93.21%) exceeded the cut-off score for probable post-traumatic stress disorder (PTSD), have severe depressive symptoms, anxiety symptoms, and stress. The respondents in this study reported a moderate degree of forgiveness. While controlling demographics and relationship history, the partial least squares structural equation modeling analysis showed that high degree of forgiveness tends to decrease psychological health concerns through lower levels of infidelity-related posttraumatic symptoms. The findings of this study highlighted the role of forgiveness in mental health outcomes which may lead to psychotherapeutic approaches incorporating this construct.